Library management in disruptive times skills and knowledge for an uncertain future - O'Connor, Steve (Facet, 2018)
Library Management in Disruptive Times identifies the key skills and attitudes needed by the library leaders of today and tomorrow and delivers a balanced view of the future of the profession. Contributed to by expert professional library leaders and educators from across the globe, this edited collection offers thought-provoking perspectives on the challenge of the current operating environment across a range of library sectors, library professional associations and geographic regions. Each author brings their own particular area of expertise and perspective on to consider the effects of disruptive change in libraries globally